Pemberdayaan PKK Desa Lebak melalui Aplikasi WoTaS untuk Mewujudkan Green Economy - Yayan Adi Saputro; DS Drajad Wibowo; Hamidaturrohmah Hamidaturrohmah; Achmad Ridwan; Noor Azizah; Meilia Khasanah Putri (Lamahu: Jurnal Pengabdian Masyarakat Terintegrasi, 2026)
The development of a green economy in rural areas requires active community participation, particularly from women’s groups, supported by digital transformation and environmentally friendly technology. However, the Women’s Welfare Movement Group (PKK) of Lebak Village, Jepara Regency, faces several challenges, including reliance on conventional agricultural practices, low digital literacy, and the absence of online media for promoting local agricultural products. Therefore, this community service program aimed to empower PKK members through the application of aquaponic technology and the utilization of the Wonderful Taman Sari (WoTaS) digital application to enhance productivity and support sustainable economic practices. The program employed a participatory–educative approach implemented in five stages: socialization, aquaponic technology training, WoTaS application training, intensive mentoring, and evaluation. The results demonstrated a substantial improvement in participants’ knowledge and skills, with an average achievement rate of 91.9%. All participants (100%) were able to operate a simple aquaponic system, while 80% successfully used the WoTaS application independently to promote local products. In conclusion, this program effectively increased community productivity and digital literacy while strengthening the role of rural women in supporting a sustainable green economy.